2019
DOI: 10.1177/0300060519862067
|View full text |Cite
|
Sign up to set email alerts
|

Public health concerns regarding sporadic Creutzfeldt–Jakob disease in China: a case series

Abstract: In this study, we report three cases of sporadic Creutzfeldt–Jakob disease in China, two confirmed cases and one probable case. The aim of this study was to enrich the data regarding clinical and epidemiological features of this disease and to provide reference for the diagnosis, control, and prevention of sporadic Creutzfeldt–Jakob disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Among these cases of sCJD, only 0.31% (4/1302) were definitive diagnostic cases (6). Nonetheless, scientific and technical advances have facilitated great progress in the development of non-invasive methods for diagnosing sCJD, which may be one of the reasons why the reported incidence of CJD has increased each year in China (6). Compared with cerebral CT, DWI and FLAIR MRI are considered sensitive imaging tools for making the clinical diagnosis of CJD worldwide (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these cases of sCJD, only 0.31% (4/1302) were definitive diagnostic cases (6). Nonetheless, scientific and technical advances have facilitated great progress in the development of non-invasive methods for diagnosing sCJD, which may be one of the reasons why the reported incidence of CJD has increased each year in China (6). Compared with cerebral CT, DWI and FLAIR MRI are considered sensitive imaging tools for making the clinical diagnosis of CJD worldwide (7).…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization ( 5 ), brain biopsy is the only tool for obtaining a definitive diagnosis of CJD, but it is hardly accepted by patients' families and it is less used clinically due to its invasiveness. It has been reported that there were 1,464 cases of CJD and 1,302 cases of sCJD between 2006 and 2017 in China ( 6 ). Among these cases of sCJD, only 0.31% (4/1302) were definitive diagnostic cases ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation